Analisis Yuridis Fenomena Persaingan Tidak Sehat Dalam Praktik Jabatan Notaris - Edgar, Carissa Vania; Utama, Yos Johan (Faculty of Law, Diponegoro University, 2026)
The rapid growth in the number of Notaries in Indonesia has triggered unfair competition phenomena oriented toward the commercialization of legal services, threatening the dignity of the position as an officium nobile. This research aims to analyze the qualifications of actions categorized as unfair competition and the legal impacts and sanctions arising for violators to provide legal certainty for the public. The issues raised focus on ethical boundaries in professional practice and the effectiveness of regulations in suppressing malpractice. This research is expected to serve as a guideline for strengthening professional supervision to maintain the nobility of the Notary position. The research method used is normative legal research with a statutory approach and a conceptual approach. The research results indicate that unfair competition qualifications include